Task process reference model on elderly's lifestyle for cluttered homes of the elderly in Northern Thailand - Nopasit Chakpitak (2018)
Copyright © 2015 Inderscience Enterprises Ltd. The cluttered home conditions are a significant risk of falling in older people who spend most of the time in their house. Therefore, this study proposes new elderly's lifestyle task model (ELTM) with risk assessment method under scoping of the quality concept. The research was conducted in Sri Bua Ngern Village, Tha Sala District in Chiang Mai, Thailand. The basic activity of elderly lifestyle in the house was analysed, verified and validated into daily tasks. Then, the elderly risky lifestyle task of the cluttered home management was evaluated to find the maturity level. The maturity level in the elderly risky lifestyle task was increased by implementing 5S practice. This research exercise shows clearly that the ELTM reference model represents daily living tasks of the elderly in their own house. In addition, the five levels of maturity assessment can measure the elderly's capability in preventing the risk of falling.